Business Development Strategy Of Insan Bandrek Red Ginger From The Maqashid Shariah Perspective - Wahyuni, Sri; Arif, Muhammad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the national economy, requiring well-planned strategies for sustainable development. This study aims to analyze business development strategies and income growth from the perspective of Maqashid Shariah. The research focuses on the Insan Bandrek Jahe Merah product, with data analyzed using SWOT analysis. The findings indicate that the Insan Bandrek Jahe Merah business is positioned in Quadrant II of the SWOT diagram, with coordinates X=1.09 and Y= -0.1. This placement suggests that the most appropriate business development strategy is diversification. Diversification can be implemented through product innovation, such as introducing new products suitable for consumption in hot weather or utilizing alternative raw materials. Additionally, another crucial strategy involves emphasizing the uniqueness of raw materials and obtaining business licenses to create differentiation from competitors. In terms of marketing, digital media promotion through Facebook Ads, Instagram Ads, TikTok, and e-commerce platforms is essential for expanding market reach. From the perspective of Maqashid Shariah, business development strategies must align with the principles of protecting religion (deen), property (maal), intellect (aql), life (nafs), and lineage (nasl), ensuring ethical and sustainable business growth.